Occult hepatitis B infection among vaccinated cohort - Shuaibu, Hudu Abdullahi; Sekawi, Zamberi; Mohd Taib, Niazlin; A. Malik, Yasmin; Mohammed Harmal, Nabil Saad (Blackwell Publishing, 2013)
BACKGROUND: